Learn about Probolinggo Municipal Government Partnership Pattern with Corporate CSR in order to Realize Probolinggo City Environmentally Friendly - Qurotal Aini; Wahyudi Winarjo; M. Masduki (Universitas Muhammadiyah Malang, 2018)
The existence of industry in a city has an important role in the survival of society. Industry managers, as well as industrial environment are closely related to the regional government, because it is one of the planning of the city layout of an area. The importance of maintaining good relations has been realized by every company. How they foster good relations with the local government, the community, and the environment around the company. The existence of CSR (Corporate Social Responsibility) helps the company to establish such good relationships, besides the mutually beneficial relationships between companies and communities, companies with local governments that such things can help mitigate and minimize conflicts that occur. In the drafting of Perda CSR, the DPRD and the government sometimes do not pay attention to the parties who become the object subject to the responsibility of Perda, in this case the company. The government should understand the construction of corporate thinking, because it will be contradictory when on the one hand the region seeks to attract investors to invest their capital, while on the other hand due to too many rules, formal and informal costs, even make investors reluctant to invest. In this research use social control theory, and social action, also institutionalism organizational.In this study using the type of qualitative research with phenomenology approach which of the phenomenon is doing an observation, then use field notes as well as in-depth interviews of informants who are selected based on purposife. The data obtained will be analyzed using qualitative descriptive technique and the data is checked for validity by triangulation.